A survey of Sta. Rosa, a rural barrio and its school - Maminta, Rosario E. 1922- ([Quezon City University of the Philippines], 1952)
The rural life and rural education in Barrio Sta. Rosa, Sta. Maria, Pangasinan is the subject of this study. The researcher analyzed the different phases of the community, its history and physical setting, economic conditions and human resources, its social structure, its health practices and its religion.
Bibliography: p. 152-153.
Thesis (M.Ed.)--University of the Philippines, 1952
Typewritten
Vita
Keywords: Rosa, Sta. Maria, Pangasinan; Community and school